Walter the baker; an old story retold and illustrated by Eric Carle. - Carle, Eric. (Knopf, 1972)
Through chance, the baker produces the first pretzel and redeems himself with the king.
Through chance, the baker produces the first pretzel and redeems himself with the king.
14
Keywords: Bakers / Fiction.